Elaboração, aplicação e avaliação de recurso didático para alunos com deficiência visual no ensino médio - Paulino, Ana Laura de Souza (Universidade Federal de São Carlos, 2014)
This study aimed to develop an educational model of the DNA molecule and evaluate the use of such adapted teaching resource in the classroom for students with visual impairments and visionaries After completion of the preparation of the material, a pilot was conducted with two blind people before starting the data collection phase. This research was conducted with 30 participants, distributed as follows: three university professors in the field of cell biology, three university professors in the field of biology education, three special education teachers, three biology teachers of the rooms of the students, three students with disabilities visual (blindness or low vision); seers and fifteen students in a classroom of high school, five of each room of students with visual impairments participant. Data collection was conducted in three schools through interviews and questionnaire produced with semi - structured questions applied to teachers, students and visionaries students with visual impairments who have identified the suitability of the resource for use. The teaching resource was built with contrasting colors and textures, since the perceptual framework of students with total blindness and low vision are distinct. Participating teachers made a preliminary assessment of the material prior to application and review with students. The evaluation with teachers of cell biology was taken to analyze the material for their conceptual representation of the content discussed. The teachers teaching biology reviewed the material and its conceptual representation and features that can aid learning in biology courses of high school. The special education teachers have analyzed the material with regard to ease of handling, colors and shape of the structures, as well as the suitability perceptual framework of students with low vision and blindness. Students with visual impairments rated the material and characteristics that aid learning, ease of use and format of the material, ie, whether it was appropriate to their perceptual framework. Evaluation with the visionaries students is justified because the courseware is a resource that teachers can use to assist the learning process of the students present in the classroom in regular education. Thus, despite the material produced have adapted to the perceptual characteristics of referential students with visual impairments, it can also be used with students visionaries, thus favoring the search for building a democratic school. The resource was developed as an appropriate reference to the perceptual and the potential to contribute to the effective inclusion of the visually impaired. Thus it is necessary the development of tailored educational materials addressing issues not only biology, but also in other disciplines provides an improvement in inclusive process of students with visual impairments.
Preparation, implementation and evaluation of appeal for teaching students with visual impairment in secondary education.
Keywords: Educação especial; Deficiência visual; Material didático; Ensino médio; Special education; Visual impairment; Learning materials; High school; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL